Personality and Personality Disorders in Urban and Rural Africa: Results from a Field Trial in Burkina Faso - Rossier, Jérôme; Ouedraogo, Abdoulaye; Dahourou, Donatien; Verardi, Sabrina; Meyer de Stadelhofen, Franz (Frontiers in Psychology, 2013)
Several studies have observed that the structure underlying both normal personality and personality disorders is stable across cultures. Most of this cross-cultural research was conducted in Western and Asian cultures. In Africa, the few studies were conducted with well-educated participants using French or English instruments. No research was conducted in Africa with less privileged or preliterate samples. The aim of this research was to study the structure and expression of normal and abnormal personality in an urban and a rural sample in Burkina Faso. The sample included 1750 participants, with a sub-sample from the urban area of Ouagadougou (n = 1249) and another sub-sample from a rural village, Soumiaga (n = 501). Most participants answered an interview consisting of a Mooré language adaptation of the Revised NEO Personality Inventory and of the International Personality Disorders Examination. A sub-sample completed the same instruments in French. Demographic variables only have a small impact on normal and abnormal personality traits. The structure underlying normal personality was unstable across regions and languages, illustrating that translating a complex psychological inventory into a native African language is a very difficult task. The structure underlying abnormal personality was stable across regions, scales reaching even metric equivalence. As scalar equivalence was not reached, mean differences cannot be interpreted. Nevertheless, these differences could be due to an exaggerated expression of abnormal traits valued in the two cultural settings. Our results suggest that studies using a different methodology should be conducted to understand what is considered, in different cultures, as deviating from the expectations of the individual’s culture, and as a significant impairment in self and interpersonal functioning, as defined by the DSM-5.